Shark Hunting: International Trade and the Imminent Extinction of Heterogeneous Species - Tobias Erhardt; Rolf Weder (University of Basel, Center of Business and Economics (WWZ), 2015)
This paper examines the unprecedented decimation of sharks. We develop a Ricardian Gordon-Schaefer model with a continuum of heterogeneous species which are subject to combined harvesting and perfect substitutability in consumption. The model implies that slow-growing species, surviving in autarky, will be driven to extinction in an open trade regime. In the empirical analysis, we show that the model is in line with observations of shark biology and the international shark market. In particular, the likelihood of extinction turns out to be significantly greater for shark species which are part of trade in shark fins and exhibit low intrinsic growth.
Keywords: F14; F18; Q27; Q57; 330; Sharks; Trade and Renewable Resources; Biodiversity